FOREIGN POLICY OF J. KENNEDY: THE PERSONAL FACTOR IN THE COOPERATION BETWEEN THE PRESIDENT AND SECRETARY OF STATE D. RUSK - Tetiana Klynina (Американська історія і політика)
The proposed article is devoted to the figure of Secretary of State Dean Rusk during the presidency of John F. Kennedy in 1961–1963, with special attention to the interpersonal relationship between him and the president.